ADAPTIVE LEARNING SYSTEM BASED ON DESIGN THINKING TECHNIQUES - Adigun, Taiwo; Sodiq, Kazeem; Eweoya, Ibukun; Ajayi, Oluwabukola F.; Akande, Oyebola; Ayankoya, Folashade; Adetunji, Olusogo (FUDMA JOURNAL OF SCIENCES, 2025)
In today’s fast-paced and ever-evolving educational landscape, students, lecturers, professionals, and researchers often struggle with traditional learning methods that do not cater for individual learning preferences. Conventional systems fail to adapt to the varying cognitive abilities of learners, leading to inefficiencies in knowledge retention and skill development. To address this challenge, the Adaptive Learning System Based on Design Thinking Techniques was developed. This system leverages the principles of design thinking to create a personalized learning experience tailored to individual learners. By integrating adaptive learning models, the system dynamically adjusts learning materials based on user interaction, performance, and feedback. It provides real-time assessments, interactive content recommendations, and personalized learning pathways that evolve as the learner progresses. Experimental results demonstrate that the system significantly improves engagement and knowledge retention by offering a flexible, student-centered approach. By integrating design thinking technique, the learning process becomes more innovative, problem-driven, and user-focused, ensuring that learners not only acquire knowledge but also develop critical thinking and problem-solving skills essential for real-world applications.